Aggregation‐Enhanced Photoluminescence and Photoacoustics of Atomically Precise Gold Nanoclusters in Lipid Nanodiscs (NANO2). (13th December 2020) - Tahmasbi Rad, Armin; Bao, Yue; Jang, Hyun‐Sook; Xia, Yan; Sharma, Hari; Dormidontova, Elena E.; Zhao, Jing; Arora, Jaspreet; John, Vijay T.; Tang, Ben Zhong; Dainese, Tiziano; Hariri, Ali; et al.
Abstract: The authors designed a structurally stable nano‐in‐nano (NANO 2 ) system highly capable of bioimaging via an aggregation‐enhanced NIR excited emission and photoacoustic response achieved based on atomically precise gold nanoclusters protected by linear thiolated ligands [Au25 (SC n H2 n +1 )18, n  = 4–16] encapsulated in discoidal phospholipid bicelles through a one‐pot synthesis. The detailed morphological characterization of NANO 2 is conducted using cryogenic transmission electron microscopy, small/wide angle X‐ray scattering with the support of molecular dynamics simulations, providing information on the location of Au nanoclusters in NANO 2 . The photoluminescence observed for NANO 2 is 20–60 times more intense than that of the free Au nanoclusters, with both excitation and emission wavelengths in the near‐infrared range, and the photoacoustic signal is more than tripled. The authors attribute this newly discovered aggregation‐enhanced photoluminescence and photoacoustic signals to the restriction of intramolecular motion of the clusters' ligands. With the advantages of biocompatibility and high cellular uptake, NANO 2 is potentially applicable for both in vitro and in vivo imaging, as the authors demonstrate with NIR excited emission from in vitro A549 human lung and the KB human cervical cancer cells. Abstract : The rational design of NANO 2 as an imaging/theranostic platform is presented.